Pengaruh Return on Equity, Current Ratio, dan Debt to Equity Ratio Terhadap Financial Distress Pada Perusahaan Sub Sektor Consumer Service Yang Terdaftar di BEI Tahun 2018-2022 - Syarof, Rizalda Anjach; Handayani, Anita; Alkusani, Alkusani (Universitas Muhammadiyah Gresik, 2024)
Background – In the current era of globalization, business competition is increasingly fierce and has a significant impact on economic development. Global economic instability ultimately creates challenges in national economic development, especially in the ability of the business sector to develop and maintain its business prospects. Based on data from the Indonesian Stock Exchange (BEI), there are 32 companies in the consumer services sub-sector in the 2018-2022 period that are indicated to be experiencing financial distress. Objective – This research aims to determine the effect of return on equity, current ratio and debt to equity ratio on financial distress in consumer services sub-sector companies listed on the IDX in 2018 – 2022. Design / Methodology / Approach – The research method uses quantitative research methods with a sample of 105 companies using purposive sampling technique. The analytical tool used is logistic regression using the SPSS 25 program. Findings – The results of this research show that return on equity has no negative effect on financial distress, current ratio has no positive effect on financial distress, debt to equity ratio has no negative effect on financial distress. Research Implication – This research can help company managers in designing more effective financial strategies and these findings can provide insight to investors in choosing shares or companies that have a lower risk of financial distress. Investors can use it to analyze the company's financial health before investing. Limitations – This research was only conducted on sub-consumer service companies and used several limited sector variables so it did not cover all important aspects in assessing financial distress. Background – In the current era of globalization, business competition is increasingly fierce and has a significant impact on economic development. Global economic instability ultimately creates challenges in national economic development, especially in the ability of the business sector to develop and maintain its business prospects. Based on data from the Indonesian Stock Exchange (BEI), there are 32 companies in the consumer services sub-sector in the 2018-2022 period that are indicated to be experiencing financial distress. Objective – This research aims to determine the effect of return on equity, current ratio and debt to equity ratio on financial distress in consumer services sub-sector companies listed on the IDX in 2018 – 2022. Design / Methodology / Approach – The research method uses quantitative research methods with a sample of 105 companies using purposive sampling technique. The analytical tool used is logistic regression using the SPSS 25 program. Findings – The results of this research show that return on equity has no negative effect on financial distress, current ratio has no positive effect on financial distress, debt to equity ratio has no negative effect on financial distress. Research Implication – This research can help company managers in designing more effective financial strategies and these findings can provide insight to investors in choosing shares or companies that have a lower risk of financial distress. Investors can use it to analyze the company's financial health before investing. Limitations – This research was only conducted on sub-consumer service companies and used several limited sector variables so it did not cover all important aspects in assessing financial distress.